Burden of breast cancer in Bangladesh-current and future and financing treatment with link to willingness to pay - Shamsi, Tasdidaa (International Journal Of Community Medicine And Public Health, 2021)
Breast cancer is the most common cancer type among females worldwide affecting 1 in 8 women. As of 2015, breast cancer is still a leading cancer of women in Bangladesh. It has become a hidden burden which accounts for 69% death of women within the country. The rate grows up day to day due to unawareness of the people, lack of confidence about medical treatment, improper screening, maltreatment, and lack of motivation to go for institutional treatment and management. The treatment options for breast cancer are relatively very expensive. People may be willing to sacrifice overall health to channel resources towards high priority disease areas, such as cancer to improve overall life. It is highly appropriate now to link treatment fall out and finances to the patient population. This short communication adopts a descriptive approach. First, it looks at the prevalence of breast cancer in Bangladesh, how breast cancer can be managed, how treatment can be financed and willingness to pay by individuals. This article finds that the screening can be optimized as the treatment options for breast cancer are relatively very expensive in a low resourced country such as Bangladesh. Data should be disseminated among the concerned stakeholders including the women susceptible to breast cancer, the patients, the care-givers, doctors, other health-care workers and policy-makers for better management. Improving the cancer scenario overnight is not an easy task but policy makers may become interested and push this agenda forward, if the huge health impact and economic loss caused by cancer become evident to them.